Crafting a Place of Transition: From Refuge to Reconnection - Czech, Sasha (School of Architecture, Planning and Geomatics, 2024)
The feelings evoked by sterile, socially isolating clinical settings are counterproductive in biopsychosocial healthcare environments such as addiction treatment, where the survival of the individual depends not only on the treatment of their medical needs, but also on helping them rebuild their social and psychological health. This dissertation proposes a language for an inpatient addiction treatment centre that disrupts the highly controlled, institutional design cues that have come to characterize so many places of healthcare. Because this kind of facility is inherently a transitional in nature, it needs to accommodate a variety of spaces that cultivate a sense of refuge, a sense of community and ultimately a sense of independence. It needs to be a place that nurtures and holds the body, but also acclimatizes and engages, to prepare people for whatever circumstances they may face when they leave. A phenomenological lens is used to investigate how architecture can allow people to slow down, engage the senses and feel a sense of community and connection. By celebrating the sensory qualities of dynamic sunlight and nature, this architectural response endeavors to create reciprocal encounters between individuals and their immediate environment. To combat the institutional feelings evoked by large-scale dorms and mess halls, this building uses mat building principles and cues from Aldo van Eyck's Amsterdam Orphanage. The communal spaces are broken down into smaller parts and dispersed throughout the facility to create a village-like environment in which each courtyard or ‘street' has its own small-scale residential, therapeutic and recreational components. Each cluster has its own unique character – the scale, sunlighting, nature density and proximity to the centre all determine whether they evoke feelings of hiding or revealing, withdrawing or engaging, protecting or challenging.